The impact of COVID-19 on the hotel supply chain management - Milovanović, Vesna; Paunović, Mihailo; Avramovski, Stefan (Hotel and Tourism Management, 2021)
The COVID-19 virus pandemic appeared to be a low-probability, high-impact event that has caused significant disruptions in supply chains worldwide. The hotel industry has been one of the most severely affected, with all participants in the supply chain suffering from the crisis. This paper aims to analyze if, and to what extent, hotels in the Republic of Serbia have faced difficulties in supply chain management (SCM) due to the COVID-19 virus pandemic, with special reference to the difficulties in introducing information and communications technologies (ICTs) for SCM. Empirical research was conducted in May, 2021 involving managers from 40 hotel companies categorised as 4- and 5–star. The study results reveal that majority of hotel companies have experienced difficulties in SCM and implementation of ICTs for SCM due to the pandemic, while the intensity of difficulties is not found to be correlated with hotel size, category and affiliation.